Challenges to Construct Regional Knowledge Maps for Territories' Sustainable Development - Garcia-Alsina, Montserrat; Wartena, Christian; Lieberam-Schmidt, Sönke (Knowledge Discovery, Knowledge Engineering and Knowledge Management, 2015)
Knowledge management in organizations is a practice progressively implemented during the last decades. Their value is recognized as an asset to generate competitive advantage. This article translates the knowledge management’s potentials to a geographic territory, and explores how to apply to a territory the framework developed by knowledge management discipline to be applied in companies. The main point is how to build regional knowledge maps to satisfy needs expressed by some actors involved in regional policy and innovation in a territory. This work reports a research in progress, whose objective is to define a methodology to efficiently design territorial knowledge maps. It presents the theoretical background offered by other disciplines that could support knowledge management discipline. These disciplines are on the one hand, regional innovation systems and competitive - territorial intelligence, to explore components involved in a territory, and on the other hand text mining to extract information of big volumes of data contained in diverse sources of information related to a region. It shows also the theoretical framework designed to deal with this research, that identify which components should collect a regional knowledge map (structures, actors, infrastructures, resources and social capital), and how to study the contexts where knowledge is created to innovate and contribute to the regional development. Finally this paper summarizes the potentials and the challenges to construct regional knowledge maps, which constitutes sub lines of research.